Determination of Sex in Simarouba Glauca Through Molecular Marker for Improved Production - Prasanthi, L.; Bhaskara Reddy, B. V.; Rekha Rani, K.; Maheswara Reddy, P.; Rajeswari, T.; Sivaprasad, Y.; Raja Reddy, K. (Indian Forester, 2011)
A total of 250 random oligonucleotide primers were surveyed to identify sex of Simarouba glauca a tree born oilseed crop. Primer OPA-OS900, was found to produce a consistent marker, which differentiated female from both male and andromonoecious sex plants. An identified random amplified polymorphic DNA (RAPD) marker, OPA-OS, linked to male sex in Simarouba was cloned and sequenced. Their end sequences were used to design an allele-specific sequence characterized amplicon region (SCAR) primer SCAR(12f/r), which was found promising in male and andromonoecious sex. The marker designed was amplified at a specific site of 915 bp only in male and andromonoecious plants. This would help to identify the sex of tree born oilseed crop Simarouba.